Pengaruh Firm Size dan Investment Opportunity Set Terhadap Firm Value Dengan Variabel Moderasi Earning Quality - Zenabia, Tsarina; Falih , Latifah Safara (Journal of Economics, Bussiness and Management Issues, 2024)
The purpose of this study is to analyze the effect of firm size and IOS on firm value with earning quality as a moderator. The independent variables in this study are firm size and IOS, the dependent variable is firm value while earning quality is used as a moderating variable. This study uses quantitative methods and secondary data. Data was obtained from infrastructure sector companies listed on the Indonesia Stock Exchange in 2019-2023. The data was analyzed using the moderated regretion analysis method and the results of the study indicated that firm size had a significant negative effect on firm value, IOS had a significant positive effect on firm value, earning quality moderated the effect of IOS and firm value in a negative direction, while in the relationship between firm size and firm value, the earning quality moderating variable was unable to moderate the effect of firm size on firm value. The size of the firm does not reflect the productive use of assets, but choosing the right investment can increase the company's profits. High investment if accompanied by low earning quality can increase the use of debt, thereby reducing firm value.